2017
DOI: 10.1108/rsr-06-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Reference management software preferences among liberal arts faculty

Abstract: Purpose-The purpose of this study was to determine faculty preferences and attitudes regarding reference management software (RMS) to improve the library's support and training programs. Design/methodology/approach-A short, online survey was emailed to approximately 272 faculty. Findings-Survey results indicated that multiple RMS were in use, with faculty preferring Zotero over the library-supported RefWorks. More than 40 per cent did not use any RMS. Research limitations/implications-The relatively short leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
0
18
0
3
Order By: Relevance
“…Some other researchers looked at the use of RMS to store and/or annotate PDFs (Emanuel, 2013;Francese, 2012Francese, , 2013Melles & Unsworth, 2015), but they did not investigate the interest of some of the new features like syncing to mobile devices, the use of a watch folder or renaming of files. Lonergan (2017) found that annotating and highlighting uploaded documents were not that important to liberal arts faculty that were surveyed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some other researchers looked at the use of RMS to store and/or annotate PDFs (Emanuel, 2013;Francese, 2012Francese, , 2013Melles & Unsworth, 2015), but they did not investigate the interest of some of the new features like syncing to mobile devices, the use of a watch folder or renaming of files. Lonergan (2017) found that annotating and highlighting uploaded documents were not that important to liberal arts faculty that were surveyed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…RMS, on the other hand, enables researchers to store, arrange, output, and share their references. Another RMS definition is by Lonergan "a software that stores citations in a digital form, either on a local computer or via an online interface, to make organizing research and formatting bibliographies and in-text citations more efficient" (p. 2) [5]. Thus, the key functions of RMSs are to create a citation database, with the ability to track and arrange the references, and to format references and citations while writing a document.…”
Section: Reference Management Softwarementioning
confidence: 99%
“…In the United States, Lonergan [5] investigated the preferences and attitudes towards RMSs among the Liberal Arts faculty. Of the respondents, 43% did not use RMSs.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Even fewer studies examined the importing functions of the software (Table 1) (Basak, 2014a;Basak 2014b;Gilmour & Cobus-Kuo, 2011;Homol, 2014;Sergiadis, 2018a;Sergiadis, 2018b). Importing is an essential function for IR managers as well as users collecting and organizing their research (Emanuel, 2013;Francese, 2013;Lisbon, 2018;Lonergan, 2017;Madhusudhan, 2016;Melles & Unsworth, 2015;Nariani, 2016;Nilashi, Ibrahim, Sohaei, Ahmadi, & Almaee, 2016). Studies that imported citations in order to compare RMS had mixed results on which one performed the best, but all concluded that no RMS is perfect (Basak, 2014a;Basak 2014b;Gilmour & Cobus-Kuo, 2011;Homol, 2014).…”
Section: Zotero and Reference Management Softwarementioning
confidence: 99%